Makna Denotasi dan Konotasi dalam Film Animasi Amīrat al-Rūm Karya Hadi Mohammadian: Semiotika Roland Barthes - Miya Maulidiyah (Universitas Negeri Jakarta, 2021)
This article aims to describe the meaning of denotation and connotation in the animated film Amīrat al-Rūm by Hadi Mohammadian using the semiotic theory of Roland Barthes. Barthes explained that in the meaning of the word, there are two parts, denotation, namely the original meaning contained in the dictionary, and connotation, where this meaning involves human emotions and thoughts. This type of research is descriptive qualitative research, and the data source used is the animated film Amīrat al-Rūm by Hadi Mohammadian. The data collection technique uses watching, listening, and translating. Meanwhile, the data analysis is linguistic messages, unencoded iconic messages, and encoded iconic messages. The results of this study indicate that in the animated film Amīrat al-Rūm many dialogues contain denotative and connotative meanings.